Public Relations Strategy of Health Service in Socializing Covid-19 Vaccination Program - Zikri Fachrul Nurhadi; Haryadi Mujianto; Dwi Novianti Rusliani (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2022)
This study aims to explain the planning, implementation and evaluation of programs carried out by the Public Relations Department of Health in disseminating the Covid-19 vaccination program in Garut Regency. This study uses a descriptive method with a qualitative approach. Data collection techniques were carried out by interview, observation and literature study. The results showed that the program planning carried out by the Public Relations Office of the Garut Regency Health Office by analyzing the situation by interviewing all elements of society. The results of the evaluation of the program that have been carried out have caused a quick reaction, especially in enthusiasm, understanding and awareness of the importance of vaccines. The media make a very big contribution in providing understanding, especially on misinformation, but with intense socialization it can change people's thoughts and actions..